The Study of Crime in the Process of Buying and Selling Land Plots - Raden Yonanta Edy Pranawa; Siti Rodhiyah Dwi Istinah; Arpangi Arpangi (Law Development Journal, 2022)
The purpose of this research is to examine, criminal acts in the process of buying and selling land plots in accordance with existing laws and regulations, where the approach method used is the normative juridical method. The conclusion from the following research results, that the problem of buying and selling land in plots does not cause problems when carried out in accordance with laws and regulations, where the sale and purchase of land by plots can only be carried out after the buyer has paid in full the parcel of land that has been purchased and has transferred the land to be the name of the New Land Buyer/Developer. Then the new developer checks the status of land use, makes a Site Plan that is submitted to the BPN, then processes the sale and purchase of land by plot at PPAT. If the sale and purchase does not comply with existing regulations, it will impact to regulation or the law which ruled on it. The police should focus on the case which connected with the criminal actor or corporation on it.